NGS coverage accurately predicts MET and HER2 (ERBB2) gene amplifications in a real-world non-small cell lung cancer cohort - Adam Kowalewski; Adam Kowalewski; Adam Kowalewski; Janna Siemanowski-Hrach; Thomas Stehle; Jan Rehker; Udo Siebolts; Sabine Merkelbach-Bruse; Carina Heydt (Frontiers in Oncology)
BackgroundFluorescence in situ hybridization (FISH) is the current standard for detecting gene amplifications, yet its low throughput and practical constraints call for alternative methods. This study evaluates next-generation sequencing (NGS) as a potential tool for accurately predicting gene amplifications.MethodsWe analyzed 66 primary non-small cell lung cancer (NSCLC) samples, tested by both NGS and FISH. FISH was conducted to detect gene amplifications in MET in 26 samples, in HER2 (ERBB2) in 21 samples, in PIK3CA in 9 samples, and KRAS in 9 samples, with one tumor tested for both MET and ERBB2. NGS fold changes, reflected by gene coverage, were calculated as the ratio of the highest gene-specific coverage to the mean coverage across all genes.ResultsAmplification was detected in 46 (68.7%) samples. NGS fold changes correlated strongly with FISH Gene/CEN ratios (Spearman’s ρ = 0.720, p < 0.001) and gene copy number per cell (Spearman’s ρ = 0.847, p < 0.001). Among FISH-negative cases, NGS fold change ranged from 0.57 to 1.95, while in FISH-positive cases, it ranged from 2.11 to 25.08.ConclusionNGS fold changes demonstrate significant correlation with FISH metrics, supporting NGS as a promising marker for gene amplification. A fold change cutoff of 2.0 effectively distinguishes amplified from non-amplified cases, with NGS achieving a high degree of predictive reliability across the tested genes.